Guide to Domain Specific Language Graphical Editor Prototyping - Rabii, Anass; Assoul, Saliha; Roudiès, Ounsa (Computer Assisted Methods in Engineering and Science; Vol 28 No 3 (2021), 2022)
Model-based systems engineering (MBSE) is a methodology that supports the use of models to better analyze and understand complex systems and create quality and costefficient products. The analysis is facilitated by platforms that support formal graphical modeling and provide complementary modules for testing, validation, code or documentation generation. Thus in specialized fields, researchers create domain-specific languages (DSLs) for their niche purposes. In systems engineering, these DSLs can be created through the extension of the standard modeling language SysML. However, these DSLs do not possess modelers unless they are renowned. Therefore, they cannot benefit from advances in the MBSE tools. Our study aims to provide a graphical editor prototype for all DSLs to allow access to the MBSE tools. Using the analytic hierarchy process (AHP) method we establish that Eclipse Papyrus is the best plugin to use due to its extensibility, the richness of the Eclipse modeling platform and ease of use. Next, we provide a step-by-step guide to incorporate any profile in SysML Papyrus as an extension allowing to model any DSL. This guide is illustrated by an example taken from the domain of urban planning.